Data Hiding in Image by Optimal Random Substitution - Nisha; Kusum (International Journal of Computer Sciences and Engineering, 2014)
The importance of reducing a chance of the Information being detected during the transmission is being an issue now days. Some solution to be discussed is how to pass information in a manner that the very existence of the message is unknown in order to repel attention of the potential attacker. Steganography comes from Greek and literally means ‘Covered writing’. Steganography is closely related to hidden channel scheme. It is the art and science of writing of hidden message in such a way that no one apart of intended recipients knows the existence of message. Steganography is often confused with cryptography because the two are almost similar in the way that they both are used to protect confidential information. The difference between the two is in the appearance in the processed output; the output of steganography operation is not apparently visible but in cryptography the output is scrambled so that it can draw attention. Applications of both are in the field of communication system, Steganography coding inside transport layer such as an MP3 file and in the defence system.